Operando X-ray tomography and sub-second radiography for characterizing transport in polymer electrolyte membrane electrolyzer. (20th June 2018) - Leonard, Emily; Shum, Andrew D.; Normile, Stanley; Sabarirajan, Dinesh C.; Yared, Dominic G.; Xiao, Xianghui; Zenyuk, Iryna V.
Abstract: Utilizing hydrogen gas as an energy carrier and enabling a hydrogen economy is a promising step towards decarbonization. Water electrolysis is a key process in hydrogen generation, but electrolyzers face a couple technological hurdles before widespread integration could occur. Understanding morphology evolution and transport processes in an operating polymer electrolyte membrane (PEM) electrolyzer is key to reducing cost and increasing efficiency. In this study, combined operando X-ray computed tomography and radiography are used to study transport and degradation in PEM electrolyzers subject to applied current densities. Tomography enables three-dimensional steady-state imaging but does not capture transport subtleties. Radiography is limited to two-dimensions but does capture transient phenomena. The tomography results depict degradation of the catalyst layer on the anode side of the electrolyzer. The rate of degradation was observed to increase as the applied current density increased. The catalyst particle detachment is due to autonomous propulsion during the oxygen evolution reaction. Particles that mechanically rip off the membrane were observed to be redeposited into the porous transport layer. During radiography, sub-second exposure time is required to capture the transient behavior of oxygen evolution, even at the lower current densities (50–200 mAcm −2 ). Various flow regimes were observed in the channel ranging from bubbly to slug flow depending on current density. Experimental observations agree with a model that an increase in current density increases oxygen bubble diameter and decreases bubble residence time within the electrolyzer channel.